ANALISIS KETERAMPILAN MENULIS SURAT RESMI MAHASISWA PGSD FKIP UNIVERSITAS RIAU - Rosti Idayanti; Zufriady Zufriady (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is a descriptive quantitative research. The purpose of this research is to describe the skills of PGSD FKIP Riau University students in writing official letters. The data collection technique is writing test. The validity of the research has been validated by experts. The sample in this study was 78 students from the 2016 to 2018 class of PGSD FKIP Riau University students. The skills of PGSD FKIP students of the University of Riau were analyzed by using categories from 12 predetermined aspects. The results show that the average of completeness of the letter parts aspect was 94.87 with a very good category, the average of writing a letter head aspect was 69.87 with a good category, the average of the letter date aspect was 79.80 with a good category, the average number of the letter aspect was 75.32 with a good category, the average of the attachment aspect was 95.19 with a very good category, the average of things / subject aspect was 89.74 with a very good category, the average of the address letter aspect was 78.52 with a good category, the average of the greeting aspect was 75.96 with a good category, the average of the contents of the letter aspect was 90.06 with a very good category, the average of closing greetings aspect was 51.28 with a moderate category, the average of writing the name of the sender aspect was 78.20 with a good category, the average of using sentences aspect was 59.61 with a moderate category. From these results, the overall average was 78.205 with a good category. This shows that the skills of writing an official letter from PGSD FKIP Riau University students are good.